Public Perceptions of Personal Data Security in Digital Service Utilization in Indonesia and Thailand: A Comparative Analysis of Regulatory Frameworks, Risks, and User Trust - Ar Rahiim Innash; Arista Candra Irawati; Vicentius Simon Suyanto; Sudijono Sastroatmodjo; Prattana Srisuk (International Journal of Applied and Scientific Research, 2026)
Digital transformation in Southeast Asia has increased public reliance on digital services while simultaneously heightening the risk of personal data breaches. This article analyzes public perceptions of data security in Indonesia and Thailand through a comparative approach covering regulations, recent incidents, and user trust frameworks. Indonesia enacted Law No. 27 of 2022 on Personal Data Protection (PDP), while Thailand has implemented the Personal Data Protection Act (PDPA) since 2022. Public perception in both countries is shaped by three key factors: digital literacy, experiences with data breaches, and the effectiveness of law enforcement. Incidents such as the hacking of the Temporary National Data Center and tax data breaches in Indonesia have heightened public concern. Conversely, the imposition of administrative fines in Thailand demonstrates stronger enforcement of accountability. Public trust is heavily influenced by transparency, incident handling, and consistent law enforcement